2017
DOI: 10.5194/acp-17-12533-2017
|View full text |Cite
|
Sign up to set email alerts
|

Merged SAGE II, Ozone_cci and OMPS ozone profile dataset and evaluation of ozone trends in the stratosphere

Abstract: Abstract. In this paper, we present a merged dataset of ozone profiles from several satellite instruments: SAGE II on ERBS, GOMOS, SCIAMACHY and MIPAS on Envisat, OSIRIS on Odin, ACE-FTS on SCISAT, and OMPS on Suomi-NPP. The merged dataset is created in the framework of the European Space Agency Climate Change Initiative (Ozone_cci) with the aim of analyzing stratospheric ozone trends. For the merged dataset, we used the latest versions of the original ozone datasets. The datasets from the individual instrumen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 59 publications
12
86
0
Order By: Relevance
“…Our results are also largely consistent with more recent profile trend studies Sofieva et al, 2017;Steinbrecht et al, 2017) that basically show mostly insignificant trends at lower stratosphere altitudes.…”
Section: Trends In Broad Zonal Bandssupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are also largely consistent with more recent profile trend studies Sofieva et al, 2017;Steinbrecht et al, 2017) that basically show mostly insignificant trends at lower stratosphere altitudes.…”
Section: Trends In Broad Zonal Bandssupporting
confidence: 82%
“…The latter would mean that the BDC is getting stronger in the SH, which would result in larger SH extratropical lower stratospheric ozone trends as compared to the NH. However, the recent stratospheric ozone profile trend studies do not indicate such a hemispheric trend asymmetry in the lower stratosphere Steinbrecht et al, 2017;Sofieva et al, 2017).…”
Section: Latitude-dependent Ozone Trendsmentioning
confidence: 98%
See 1 more Smart Citation
“…The decreasing trend in the tropical lower stratosphere, found previously by Sioris et al (2014) and Bourassa et al (2014), remains statistically significant in these updated and pointing-corrected results, although with slightly reduced extent. The trend results are very consistent with those presented by Steinbrecht et al (2017) and Sofieva et al (2017), which also use this drift-corrected OSIRIS data in combination with SAGE II, OMPS, and other limb data records.…”
Section: Impact On Trendssupporting
confidence: 79%
“…Systematic comparisons between the databases showed that the applied merging technique plays a role in the representation of realistic long-term stratospheric ozone trends and variability , in addition to the choice of data sources. Recognizing these sensitivities, a second generation of most of these databases has already been developed, with reprocessed data sources and improved merging techniques (e.g., Bourassa et al, 2018;Sofieva et al, 2017;Zawada et al, 2018). However, these updated databases still have limited coverage in the troposphere.…”
Section: Introductionmentioning
confidence: 99%